ONEIROSPHERE: LINGUISTIC AND CULTURAL ASPECTS OF DREAM - Allayev Zafar Mengboyevich (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
The concept of the Oneirosphere, or the dream realm, has been a subject of interest in linguistic and cultural studies. This article explores the linguistic structures, cultural significance, and pragmatic aspects of dream narratives in English and Uzbek traditions. By analyzing symbolic meanings, lexical variations, and discourse functions of dreams, this study provides a comparative perspective on how different cultures perceive and interpret the dream world. The findings highlight the intricate relationship between language, culture, and the subconscious, revealing that the Oneirosphere serves as both a linguistic archive and a reflection of societal worldviews.